The commissive speech act in Adele songs - Syahidah Nurul Alam; Dila Charisma; ER Winarto (English Language Education Study Program, Teacher Traning and Education Faculty, Universitas Muhammadiyah Cirebon, 2019)
The objectives of the research are to analyze speech act classification and the form of commissive speech act used in the Adele song. The approach of this study was descriptive qualitative. The researchers found 49 data based on the analyzed data, the most frequently occurring in speech act classification is commissive. Commssive occured 26 times (53, 06%), followed by expressive 13 times (26, 53 %), then representative 5 times (10, 20 %), directive 3 times (6, 12%) and declaration 2 times (4, 08 %). Then the researchers found and analyzed Adele lyric songs, based on form of commissive speech act, there are threat, refusal, promise, offer, warning, and volunteering. The researchers found and analyzed 26 data, based on the analyzed; the most frequently occurring commissive speech act is promise. Promise occured 10 times (38, 46 %), followed by offer as much 6 times (23, 07 %), then warning 4 times (15, 38%), threat 3 times (11, 53%), refusal 2 times (3, 84%) and volunteer occurs 2 times (7, 69%) Keywords: Pragmatic; Speech Act; Speech Act Classifications by Searle form of Commissive; Song